Malaysian digital painting: an art historical study / Mumtaz Mokhtar - Mokhtar, Mumtaz (Institute of Graduate Studies, UiTM, 2012)
Malaysian modern painting was established in the 1930s during British colonization. Since that period, artists applied pigments on paper and canvas, using media such as water color, oils, pastel and acrylic paint. With the advent of digital technology, local artists started using computers in their art-making in the 1980s and have become reputable since the Digital Collage exhibition in 1988. In the context of art, digital painting is an extension of the painting concept which refers to new forms involving various types of digital data including vector or raster image, text and sound.